Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) - Kodada, Jan; Hendrich, Lars; Balke, Michael (Zootaxa, 2018)
We report the discovery of the second Bidessini diving beetle species from a Venezuelan table-top mountain (also referred to as "tepui"). Tepuidessus grulai sp. nov. from Acopán Tepui can easily be separated from Tepuidessus breweri Spangler, 1981, described from Roraima Tepui, about 140 km apart from Acopán Tepui, by its much broader habitus with distinct outline discontinuity between pronotum and elytra, well developed, long and deep basal striae on pronotum and elytra and by the unbordered apical abdominal ventrite.